Business Resilience of the Muslim Merchants through of Social Capital - Lia Istifhama (Sekolah Tinggi Agama Islam Taruna Surabaya, 2022)
This study aims to determine the portrait of traditional markets that survive in the era of modern trade competition. There are three problems in this study: business resilience strategies, elements that make up social capital, and business resilience through merchants’s social capital. The research setting is the Soponyono market, which is managed by Masjid Tholabuddin Foundation. The approach in this research is phenomenology approach. Data are collected by snowball sampling technique to Muslim merchants as informants, then, are analyzed through by interactive analysis (qualitative approach). The results of the study reveal that the purpose of the muslim merchants to stay in business, is to seek halal income without worrying about modern trade competition. They practice active, passive, and networking strategies. Of the three, network strategy is considered to play an important role in business resilience. Network strategies are formed in three elements of social capital, namely: mutual trust, social networks, and reciprocity. The theory for examining this study, are Mark Granovetter's about socio-economic attachment theory, Fukuyama about elements of trust, social networks, and reciprocal actions, and Islamic theory, namely: ‘amanah, at-ta’awun, and ukhuwwah Islamiyyah.